Direct injection method and apparatus for low NOx combustion of high hydrogen fuels - PFEFFERLE, WILLIAM C (2014)
A method is provided for low NOx combustion of high hydrogen content and other fuels in gas turbines wherein at least a portion of the fuel is combusted under fuel rich conditions and a portion of resulting reaction heat is transferred to combustion air prior to non-premixed combustion of the fuel.